A interpretação e aplicação de aspectos morais no direito fundamental à liberdade de expressão: uma análise crítica da posição do Supremo Tribunal Federal no caso Ellwanger - BARROS, Caroline Maria Costa (2015)
It is growing the support to the theory that considers the necessary connection among Right and Moral, particularly when we spoke about the Fundamental Human Rights - while an ideal to be reached by all the people and for all the nations. The existence of other values is discussed for the validity of the juridical system, referring to the doubts up to where it can the moral precepts to influence of the juridical system. The present work search to study the existent dialogue between the moral norms and the juridical norms, besides the use of the moral precepts as instrument for limitation of the fundamental right to the freedom of expression, with relationship to the popularization of the speech of the hate. The systems juridical North American and German present very different solutions for cases in what the ideas racists' manifestation, prejudices and hostile to certain groups, due to race, color, religion, sex, etc. Though, as the Brazilian treatment is revealed for such a such delicate subject in a concrete way? In fact, it is making the analysis of the judgment of HC nº 82.424- 2/RS in the Supreme Federal Tribunal that she intend to verify the ministers they are used of moral arguments to limit the right to the freedom of expression and if such restrictions are legitimate, after all, if on a side we have the protection to the human dignity, not being " morally acceptable " the hostile speech and prejudice against groups of minorities, as it happened with the Jewish community, on another side, we would also have the freedom of manifesting opinions and of possessing certain ideology. In that sense, is a conciliation possible? It is in the investigation of the philosophical currents, doctrines, in the compared right and in the votes of the ministers of the Supreme Federal Tribunal that it'll look for to clear the treatment of the referred constitutional rights.